The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1093/ofid/ofy028
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Among Persons Living With HIV in Medical Care in the United States—Medical Monitoring Project, 2013–2014

Abstract: Hypertension is a leading modifiable risk factor for cardiovascular disease (CVD), and persons living with HIV are at increased risk for both hypertension and CVD. Therefore, using data from a nationally representative sample of patients living with HIV, we assessed missed opportunities for the optimal management of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 11 publications
1
12
2
Order By: Relevance
“…Some studies have shown that demographic and socio-economic factors such as age, gender, race, level of education and income are associated with hypertension in PLHIV [ 30 ]. For example a study in Ethiopia found that HIV diagnosed patients with some education and an average monthly income were significantly more likely to develop hypertension [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that demographic and socio-economic factors such as age, gender, race, level of education and income are associated with hypertension in PLHIV [ 30 ]. For example a study in Ethiopia found that HIV diagnosed patients with some education and an average monthly income were significantly more likely to develop hypertension [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…4 Elderly PLWH are at greater risk of developing chronic diseases such as hypertension and diabetes, and these conditions are increasingly prevalent in PLWH. [5][6][7] Furthermore, metabolic disease risk factors such as obesity may interact with HIV or ARV-related factors, thereby worsening existing comorbidities and/or complicating patient care. 8 Recent studies have shown that initiating ARV therapy leads to weight gain, from a few kilograms to >20% of original bodyweight, especially within the first year.…”
Section: Introductionmentioning
confidence: 99%
“…However, structural changes in the cardiac vasculature are observed as early as the first ten years of life for vertically HIV-infected subjects ( 41 ). Poorly controlled hypertension may eventually lead to cardiovascular diseases, kidney diseases, and mortality ( 42 ); hence early identification of high-risk individuals through screening is critical to prevent the development of these outcomes.…”
Section: Discussionmentioning
confidence: 99%